Regionally consistent Western North America paleomagnetic directions from 15 to 35 ka: Assessing chronology and uncertainty with paleosecular variation (PSV) stratigraphy. (1st December 2018) - Reilly, Brendan T.; Stoner, Joseph S.; Hatfield, Robert G.; Abbott, Mark B.; Marchetti, David W.; Larsen, Darren J.; Finkenbinder, Matthew S.; Hillman, Aubrey L.; Kuehn, Stephen C.; Heil, Clifford W.
Abstract: New Paleomagnetic Secular Variation (PSV) data from Fish Lake, Utah, USA, along with previously published regional records, allow us to build an independently dated Western North America PSV stack (WNAM17) from about 35 to 15 ka that quantifies dating and paleomagnetic uncertainties. In February 2014, we recovered a composite 11-m-long sediment record from Fish Lake, Utah that retrieved glacially influenced and post-glacial sediments. Computed tomography (CT) scans and magnetic susceptibility were used to build a precise depth scale, while radiocarbon dating of terrestrial macrofossils and tephrostratigraphy provide tight age-control. Glacially influenced sediments have well-defined characteristic remanent magnetizations with all maximum angular deviation values < 5°, resolving a record of Late Pleistocene PSV. Comparison to the PSV records at Bear Lake, Utah/Idaho, USA and Bessette Creak, British Columbia, Canada, which also contain terrestrial material radiocarbon age-control points, allow us to develop the WNAM17 PSV stack which considers both dating and magnetic acquisition uncertainties. We utilize a regional PSV chronostratigraphic modeling approach to assign chronology and uncertainty to the PSV signal and to evaluate the fidelity of age-control points at the site level that are difficult to objectively evaluate otherwise. The greatest strength of our age-depth model is that by approaching chronostratigraphy from a regional perspective, assuming a common geomagnetic signal, we can address sources of geologic uncertainty that would be difficult to quantify using only one site. We illustrate the potential stratigraphic opportunities using the WNAM17 PSV template through assessing the timing of paleoenvironmental and paleomagnetic events in Western North America, including the timing of glaciations in the Fish Lake and Bear Lake catchments and the stratigraphic context for the Late Pleistocene geomagnetic excursion recorded at Mono Lake. Highlights: New Stratigraphic and Paleomagnetic Data are Reported for Fish Lake, Utah, USA. Regional Paleomagnetic Secular Variation (PSV) Signals are Stacked from ∼15 to 35 ka. A Regional Age Model is Developed that Factors Magnetic and Radiocarbon Uncertainties. The WNAM17 PSV Template is Used to Provide New Perspective on Regional Chronologies.